Who's watching? : surveillance, big data and applied ethics in the digital age - Walsh, Adrian; Boucher, Sandy (Emerald Publishing Limited, 2022)
This 26th volume of Research in Ethical Issues in Organizations is a selection of papers from the 27th Annual Conference of the Australian Association of Professional and Applied Ethics with the theme 'Who's watching? Surveillance, big data and applied ethics in the digital age.' The papers in this volume critically engage with contemporary issues surrounding big data and surveillance, particularly in relation to large institutions, including corporations and government agencies. Special focus is put on the ethical issues concerning the collection and use of big data sets. Research in Ethical Issues in Organizations (REIO) is a double-blind, peer-reviewed series that publishes rigorous academic research into organizational ethics from a wide variety of disciplinary perspectives.
Keywords: Electronic surveillance -- Moral and ethical aspects.; Technology & Engineering, Data Transmission Systems -- General.; Ethical issues: scientific & technological developments.; elektronické knihy; electronic books